Low-Temperature Stress-Induced Hepatic Injury in Darkbarbel Catfish (Pelteobagrus vachelli): Mediated by Gut–Liver Axis Dysregulation - Amei Liu; Guoqing Duan; Libo Yang; Yuting Hu; Huaxing Zhou; Huan Wang (Antioxidants, 2025)
Low-temperature stress serves as a critical abiotic stressor that severely restricts fish survival, biogeographic distribution, and aquaculture productivity. Pelteobagrus vachelli, an economically significant freshwater fish species, displays marked sensitivity to low-temperature stress; however, its molecular adaptive mechanisms remain poorly characterized. In this study, we systematically investigated hepatic and intestinal cold stress responses in P. vachelli through a 7-day acute low-temperature exposure trial (6 °C and 11 °C), integrating histopathological examination, physiological–biochemical assays, metabolomics, and 16S rRNA sequencing. Histopathological observations revealed pronounced hepatic vacuolar degeneration, nuclear dissolution, and enhanced inflammatory cell infiltration under low-temperature conditions. Concurrently, immune-related enzymatic activities—including aspartate aminotransferase (AST), alanine aminotransferase (ALT), and alkaline phosphatase (APK)—were significantly elevated. Furthermore, substantial perturbations in antioxidant defense systems were detected, as indicated by altered superoxide dismutase (SOD) and glutathione peroxidase (GSH-Px) activities, alongside malondialdehyde (MDA) accumulation. Metabolomic profiling identified 539 differentially abundant metabolites, with pathway enrichment analysis highlighting marked alterations in FoxO signaling, amino acid metabolism, glycerophospholipid metabolism, ABC transporter, and Purine metabolism. Gut microbiome sequencing demonstrated cold-induced structural dysbiosis within the intestinal microbiota. Correlation analyses revealed robust linkages between hepatic injury biomarkers/metabolites and specific intestinal microbial taxa. Collectively, this study delineates the interplay between hepatic metabolic reprogramming and gut microbiota dysbiosis during cold adaptation in P. vachelli, establishing a theoretical framework for developing gut–liver axis-targeted strategies to augment cold tolerance in aquatic species.